Montmorillonite reinforced hybrid fiber bonded 3D printed implant and its preparation method and application
Through the 3D-printed implants strengthened by montmorillonite, the problem of poor bonding between the inorganic phase and the organic phase is solved by using multiple chemical reactions and intermolecular forces, and the implants with high biological activity and bone repair performance are achieved.
Patent Information
- Application Number
- CN202211644617.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-12-20
AI Technical Summary
The existing scaffolds used for bone tissue engineering have the problem of poor interface bonding between the inorganic phase and the organic phase, which affect structural stability and biological characteristics.
The 3D-printed implant is bonded with montmorillonite-strengthened hybrid fibers. Through the multiple chemical reactions and intermolecular forces of the 3D-printed scaffold with polydopamine-coated hybrid fibers, a high-strength crosslinking network structure is formed to improve the integration of the inorganic phase and the organic phase.
It significantly improves the biological activity and bone repair performance of the implant, can promote cell proliferation and bone tissue regeneration, and the bone integration effect of new bone and implant is excellent.
Smart Images

Figure BDA0004009213920000061 
Figure HDA0004294073990000011 
Figure HDA0004294073990000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomaterials and relates to a montmorillonite-reinforced hybrid fiber-bonded 3D-printed implant and a preparation method and application thereof. Background Art
[0002] With the increasing demand for biomedical materials in clinical practice, research and development of new biomaterials to better meet clinical needs has become an important topic in the field of bone regeneration and repair. Mimicking the composition and structure of natural bone matrix and preparing scaffolds with highly integrated inorganic and organic phases is a promising way to develop new biomaterials in bone tissue engineering. When preparing such scaffolds, organic polysaccharides, collagen fibers, etc. are usually used as strong adhesives and bioactivators, and inorganic materials are used as rigidity enhancement and bone induction components. At present, although some substantial progress has been made in the development of inorganic-organic hybrid scaffolds, existing scaffolds still have the problem of poor integration between the inorganic interface and the organic interface, which will directly affect the structural stability and biological properties of the scaffold.
[0003] Recently, researchers have found that polyphenol functional groups can integrate various material interfaces including metals, ceramics, polymers, tissues, etc. through various reactions, which can promote the recruitment and migration of endogenous stem cells. Using polyphenols to integrate organic and inorganic interfaces will be one of the effective strategies for interface integration and biofunctionalization. Therefore, if we can further improve the compatibility and integration between the inorganic and organic phases, improve the bioactivity of the scaffold materials, and develop scaffold materials with highly biomimetic bone matrix components and structures, we can better meet the needs of clinical practice for high-performance bone tissue repair materials, which will have a positive impact on the field of bone regeneration and repair. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a montmorillonite-reinforced hybrid fiber-bonded 3D printed implant and its preparation method and application, so as to solve the problem of poor interface bonding between the inorganic phase and the organic phase in the existing scaffolds for bone tissue engineering, improve the integration of the inorganic phase and the organic phase and improve the bone repair ability of the bone tissue engineering scaffold.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0006] A montmorillonite-reinforced hybrid fiber-bonded 3D-printed implant, comprising a 3D-printed stent with a polydopamine coating and a montmorillonite-reinforced hybrid fiber, wherein the 3D-printed stent with a polydopamine coating has micron-sized macropores that are interconnected, and the montmorillonite-reinforced hybrid fiber is bonded to the 3D-printed stent with a polydopamine coating and distributed in the micron-sized macropores of the 3D-printed stent with a polydopamine coating, thereby forming micron-sized small pores in the micron-sized macropores.
[0007] The 3D printed stent with polydopamine coating is composed of a 3D printed stent and a polydopamine coating on the surface of the 3D printed stent, and the 3D printed stent is composed of components including a 3D printed polymer material and micron-sized hydroxyapatite;
[0008] The montmorillonite-reinforced hybrid fiber is a polymer network formed by oxidation self-crosslinking of a polymer material having a catechol functional group, Michael addition reaction of the polymer material having a catechol functional group and collagen, chelation of phenolic hydroxyl groups of micron-sized montmorillonite and the polymer material having a catechol functional group, and hydrogen bonding or / and electrostatic interaction between the micron-sized montmorillonite, collagen and the polymer material having a catechol functional group; a part of the Michael addition reaction product of the polymer material having a catechol functional group and collagen and the oxidation self-crosslinking polymer material having a catechol functional group are intercalated into the montmorillonite sheets;
[0009] The polydopamine coating on the surface of the 3D printed bracket with the polydopamine coating is bonded to the collagen in the montmorillonite-reinforced hybrid fiber and the polymer material with catechol functional groups through Michael addition reaction and oxidative cross-linking reaction, respectively. The polydopamine coating on the surface of the 3D printed bracket with the polydopamine coating is bonded to the micron-sized montmorillonite in the montmorillonite-reinforced hybrid fiber through chelation, hydrogen bonding or / and electrostatic action.
[0010] In the technical solution of the above-mentioned montmorillonite-reinforced hybrid fiber-bonded 3D printed implant, the Michael addition reaction between the polymer material having catechol functional groups and collagen is mainly an addition reaction between the phenolic hydroxyl groups of the polymer material having catechol functional groups and the amino, thiol and other groups on the collagen; the chelation reaction between the micron-sized montmorillonite and the phenolic hydroxyl groups of the polymer material having catechol functional groups mainly refers to the chelation reaction between the aluminum ions, magnesium ions, etc. in the micron-sized montmorillonite and the phenolic hydroxyl groups of the polymer material having catechol functional groups. Similarly, the Michael addition reaction between the polydopamine coating on the surface of the 3D printed bracket with the polydopamine coating and the collagen in the montmorillonite-reinforced hybrid fiber refers to the addition reaction between the phenolic hydroxyl groups of the polydopamine coating and the amino, thiol and other groups on the collagen. The oxidative cross-linking reaction with the polymer material having a catechol functional group refers to the oxidative cross-linking reaction between the phenolic hydroxyl groups of the polydopamine coating and the phenolic hydroxyl groups in the catechol functional group. The chelation reaction between the polydopamine coating and the micron-sized montmorillonite in the montmorillonite-reinforced hybrid fiber mainly refers to the chelation reaction between the aluminum ions, magnesium ions, etc. in the micron-sized montmorillonite and the phenolic hydroxyl groups in the polydopamine coating.
[0011] In the technical solution of the above-mentioned montmorillonite-reinforced hybrid fiber-bonded 3D printed implant, in the 3D printed stent with a polydopamine coating, chelation can also occur between the calcium ions of the micron-sized hydroxyapatite on the surface of the 3D printed stent and the phenolic hydroxyl groups of the polydopamine coating.
[0012] In the technical solution of the montmorillonite-reinforced hybrid fiber bonded 3D printed implant, the content of the montmorillonite-reinforced hybrid fiber in the implant is preferably 20wt.% to 30wt.%, and more preferably 23wt.% to 27wt.%
[0013] In the above-mentioned technical solution of montmorillonite-reinforced hybrid fiber-bonded 3D printed implant, the montmorillonite-reinforced hybrid fiber is formed by reacting a polymer material having catechol functional groups, collagen and micron-sized montmorillonite in a mass ratio of (0.5-1):(0.5-1):(0.01-0.03).
[0014] In the technical solution of the montmorillonite-reinforced hybrid fiber-bonded 3D printed implant, the 3D printed stent with polydopamine coating is formed by soaking the 3D printed stent in a dopamine Tris-HCl buffer solution with a pH value of 8.5 to 8.8 and a dopamine concentration of 20 to 50 mol / L for 15 to 30 hours. The dopamine Tris-HCl buffer solution is obtained by dissolving dopamine in a Tris-HCl buffer solution with a concentration of 10 to 15 mmol / L and a pH value of 8.5 to 8.8.
[0015] In the technical solution of the montmorillonite-reinforced hybrid fiber-bonded 3D printed implant, the content of micron-sized hydroxyapatite in the 3D printed scaffold is 50 wt.% to 90 wt.%. In order to facilitate 3D printing molding when preparing the 3D printed scaffold, additives such as dispersants and plasticizers can also be added when preparing the 3D printing slurry.
[0016] In the technical solution of the above-mentioned montmorillonite-reinforced hybrid fiber-bonded 3D printed implant, the micron-sized hydroxyapatite is a spherical particle with a particle size not exceeding 50 μm, the size of the micron-sized montmorillonite does not exceed 50 μm, and the montmorillonite has a flaky structure.
[0017] In the technical solution of the above-mentioned montmorillonite-reinforced hybrid fiber-bonded 3D printed implant, the 3D printing polymer is a biocompatible 3D printable polymer material, including at least one of polylactic acid-co-glycolic acid, polycaprolactone, polyvinyl alcohol, polydimethylsiloxane, etc.
[0018] In the technical solution of the above-mentioned montmorillonite-reinforced hybrid fiber-bonded 3D printed implant, the polymer material with catechol functional groups is formed by grafting dopamine on a biocompatible polymer material, and the biocompatible polymer material includes hyaluronic acid, silk fibroin, gelatin, etc. The grafting rate of dopamine on the biocompatible material is 5% to 40%, preferably 5% to 20%. The molecular weight of the biocompatible polymer material as the basis for dopamine grafting modification can usually be 100 to 2000 kDa. The feasible polymer material with catechol functional groups includes at least one of dopamine-modified hyaluronic acid, dopamine-modified silk fibroin, and dopamine-modified gelatin.
[0019] In the above-mentioned technical solution of montmorillonite-reinforced hybrid fiber-bonded 3D printed implant, the collagen is type I collagen.
[0020] In the above-mentioned technical solution of montmorillonite-reinforced hybrid fiber-bonded 3D printed implant, the size of the micron-sized macropores is 500 to 1200 μm, and the size of the micron-sized small pores is 100 to 200 μm.
[0021] The present invention also provides a method for preparing the above-mentioned montmorillonite-reinforced hybrid fiber-bonded 3D printed implant, comprising the following steps:
[0022] (1) placing the dried 3D printed scaffold in a dopamine Tris-HCl buffer solution with a pH value of 8.5 to 8.8 and fully immersing it to obtain a 3D printed scaffold with a polydopamine coating;
[0023] (2) dissolving the polymer material having catechol functional groups and collagen respectively, fully mixing the obtained solution of the polymer material having catechol functional groups, the obtained collagen solution and micron-sized montmorillonite, and then adjusting the pH value to 7.0-7.4 to form a sol;
[0024] (3) immersing the 3D printed stent with a polydopamine coating in the sol so that the sol fills the pores of the 3D printed stent with a polydopamine coating, leaving the 3D printed stent with the pores filled with the sol to stand until the sol turns into a gel state, and freeze-drying to obtain a montmorillonite-reinforced hybrid fiber-bonded 3D printed implant.
[0025] In the technical scheme of the above-mentioned preparation method, the preparation method of the 3D printed bracket is: fully dispersing the components including the 3D printing polymer and the micron-sized hydroxyapatite in a solvent, and volatilizing and removing part of the solvent to obtain a 3D printing slurry, making the 3D printing slurry into a bracket by 3D printing, and drying and removing the solvent in the bracket to obtain a 3D printed bracket.
[0026] In the above preparation method, the polymer material having catechol functional groups is preferably dissolved in water to form a solution of the polymer material having catechol functional groups with a concentration of 5 to 50 mg / mL, and collagen is preferably dissolved in acetic acid solution to form a collagen solution with a concentration of 5 to 50 mg / mL.
[0027] The present invention confirms through in vitro cell experiments that the montmorillonite-reinforced hybrid fiber-bonded 3D printed implant of the present invention has no obvious cytotoxicity and can promote cell proliferation, and has good biocompatibility. The present invention confirms through animal experiments that the montmorillonite-reinforced hybrid fiber-bonded 3D printed implant of the present invention has an excellent repair effect on the critical size defect of the rabbit femoral condyle, and can promote the regeneration of the critical size defect of the rabbit femoral condyle. Not only can a large amount of new bone tissue be formed at the defect, but also the new bone grows from the defect to the center of the defect, and the bone integration effect with the implant is excellent. After 12 weeks of repair, the cortical bone part has been completely healed and reshaped, and there is no difference in the bone tissue morphology with the surrounding host. It shows that the implant has good host bone integration and bone conduction ability.
[0028] Based on the above experimental results, the present invention also provides the application of the above-mentioned montmorillonite-reinforced hybrid fiber-bonded 3D printed implant in the field of bone repair.
[0029] Compared with the prior art, the technical solution provided by the present invention produces the following beneficial technical effects:
[0030] 1. The present invention provides a montmorillonite-reinforced hybrid fiber-bonded 3D printed implant, which is bonded by a 3D printed stent with a polydopamine coating having mutually interpenetrating micron-sized macropores, and montmorillonite-reinforced hybrid fibers attached to the 3D printed stent with the polydopamine coating and distributed in its micron-sized macropores; the 3D printed stent with the polydopamine coating contains micron-sized hydroxyapatite, and the montmorillonite-reinforced hybrid fibers are formed by multiple chemical reactions of a polymer material with catechol functional groups, collagen and micron-sized montmorillonite, and there are intermolecular forces between the micron-sized montmorillonite and the polymer material with catechol functional groups and collagen; at the same time, the 3D printed stent with the polydopamine coating and the montmorillonite-reinforced hybrid fibers are also bonded together through multiple chemical reactions. On the one hand, the polydopamine coating acts as a bridge between the organic phase and the inorganic phase, and plays the role of a cross-linking center. On this basis, montmorillonite is introduced as a reinforcing phase to form electrostatic interactions, hydrogen bond interactions and chelation, thereby strengthening the cross-linking network structure, thereby improving the overall mechanical strength of the scaffold and the tissue repair effect. On the other hand, through multiple chemical reactions, micron-sized pores are formed in the micron-sized macropores of the 3D printed scaffold with a polydopamine coating, forming a hierarchical pore structure. This hierarchical pore structure can not only provide abundant attachment sites for cell adhesion and migration, but also facilitate the exchange of various nutrients and gases, and can provide a microenvironment conducive to cell and tissue growth at the implant site. The combined effect of the above two factors can effectively improve the bioactivity and bone repair performance of the implant.
[0031] 2. The montmorillonite-reinforced hybrid fiber-bonded 3D printed implant provided by the present invention has a structure similar to trabecular bone, a multiple porous structure suitable for cell growth, and the various parts of the implant are integrated together through multiple chemical bonds and intermolecular forces, and the montmorillonite is introduced to strengthen the interaction between the components, which can solve the problem of insufficient tightness of the organic polymer and the inorganic hydroxyapatite scaffold in this type of scaffold material in the prior art. At the same time, the 3D printing technology can also be used to customize the implant that matches the bone injury site, and it can also be freely cut after preparation. The use method is flexible and diversified, and it has broad application prospects in the field of bone tissue repair.
[0032] 3. The present invention has confirmed through in vitro cell experiments that the implant has no obvious cytotoxicity and can promote cell proliferation, and has good biocompatibility. It has also been confirmed through rabbit critical femoral condyle defect repair experiments that the implant can promote the regeneration of rabbit bone defects, not only can a large amount of new bone tissue be formed at the defect, but also the new bone tissue has good bone integration with the implant. It shows that the implant provided by the present invention can produce a good repair effect when used in the field of bone tissue defect repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 These are SEM images of the montmorillonite used in Example 3 at different magnifications.
[0034] Figure 2 This is the H NMR spectrum of sodium hyaluronate, dopamine and dopamine-modified hyaluronic acid prepared in Example 1.
[0035] Figure 3 It is the thermogravimetric analysis diagram of PGK, PGS and PGH.
[0036] Figure 4 It is the differential thermal analysis diagram of PGK, PGS and PGH.
[0037] Figure 5 These are the XRD test results of MMT and PGK.
[0038] Figure 6 These are the storage modulus test results of PGK hydrogel and PGH hydrogel at different frequencies.
[0039] Figure 7 It is the proliferation of cells after co-cultured with PGK, PGS and PGH for different time periods in vitro.
[0040] Figure 8 These are the FDA / PI staining results after PGK, PGS and PGH were co-cultured with cells in vitro for different periods of time.
[0041] Fig. 9 These are the results of phalloidin / DAPI staining of PGK, PGS, and PGH.
[0042] Fig.10 This is the defect repair status of PGK and PGH implanted into the critical size defect of rabbit femoral condyle 12 weeks later. DETAILED DESCRIPTION
[0043] The following examples further illustrate the montmorillonite-reinforced hybrid fiber-bonded 3D printed implant provided by the present invention, as well as its preparation method and application. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The technical personnel in the relevant field make some non-essential improvements and adjustments to the present invention according to the above invention content for specific implementation, which still falls within the scope of protection of the present invention.
[0044] Example 1
[0045] In this example, dopamine-modified hyaluronic acid (HAD) was prepared in the following steps:
[0046] (1) To an aqueous solution of sodium hyaluronate (Mw=300 kDa) at a concentration of 11.5 mg / mL, a solution of N-hydroxysuccinimide (NHS) at a concentration of 46 mg / mL was added dropwise, and then a solution of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCI) at a concentration of 150 mg / mL was added dropwise, and the mixture was stirred for 1 hour, and then dopamine hydrochloride was added and stirred for 12 hours. During the two stirring reactions, the pH value was controlled at 5 to 5.5. The operation of this step was carried out under anaerobic conditions under nitrogen protection, and the mass ratio of sodium hyaluronate, EDCI, NHS and dopamine hydrochloride was 400:766:230:230;
[0047] (2) The reaction solution obtained in step (1) is dialyzed for 72 h in ultrapure water at a pH of 4 using a dialysis membrane (Mw = 3.5-8 kDa), and freeze-dried to obtain HAD, whose structural formula is shown in formula (I), and stored in a desiccator for later use.
[0048]
[0049] Sodium hyaluronate, dopamine and HAD 1 H NMR characterization, the results are as follows Figure 2 As shown, Figure 2 The curves in the figure represent HAD, sodium hyaluronate and dopamine from top to bottom respectively. It can be seen from the figure that the characteristic hydrogen spectrum of dopamine appears near 6.8ppm in the nuclear magnetic hydrogen spectrum of HAD, indicating that HAD was successfully prepared. The grafting rate of dopamine in HAD was measured by the integration results to be about 6%.
[0050] By adjusting the mass ratio of sodium hyaluronate, EDCI, NHS and dopamine hydrochloride and the molecular weight of sodium hyaluronate, the grafting rate of dopamine in HAD can be changed. For example, the grafting rate of dopamine in HAD can be adjusted within the range of 5% to 40%.
[0051] Example 2
[0052] In this embodiment, the steps for preparing a 3D printed stent and a 3D printed stent with a polydopamine coating are as follows:
[0053] (1) Dissolving poly(lactic acid-co-glycolic acid) copolymer (PLGA) in dichloromethane, adding dispersant ethylene glycol butyl ether and plasticizer dibutyl phthalate, and mixing them uniformly to form a mixed solution, wherein the ratio of PLGA, dichloromethane, ethylene glycol butyl ether and dibutyl phthalate is 5 g:30 mL:4 mL:2 mL; adding spherical hydroxyapatite particles with a particle size not exceeding 50 μm to the mixed solution and mixing them uniformly, placing the obtained slurry in an open environment and stirring it intermittently, increasing the viscosity of the slurry by evaporation of the solvent until the viscosity of the slurry reaches a viscosity suitable for 3D printing, and obtaining a 3D printing slurry.
[0054] The 3D printing slurry has a shear-thinning viscosity characteristic and can be formed by the rapid volatilization of dichloromethane after 3D printing.
[0055] (2) The 3D printing slurry is transferred to the printing material tube of the 3D printer, and a 0 / 90 / 0 orthogonal structure bracket is printed by a direct extrusion printer. The obtained bracket is fully soaked in anhydrous ethanol and then naturally air-dried to obtain a 3D printed bracket, wherein the content of hydroxyapatite in the 3D printed bracket is 80wt.%.
[0056] The printing parameters are as follows: extrusion pressure is 0.2-0.6 MPa, printing speed is 3-20 mm / s, printing temperature is room temperature, layer height is 0.24 mm, printing wire spacing is 1 mm, and the size is a 10 mm*10 mm*10 mm cube. The aperture of the 3D printed bracket can be adjusted by adjusting the printing wire spacing, the wire diameter and the layer height. A series of 3D printed brackets of the same size are prepared in this step. In the subsequent animal experiments, if a cylindrical 3D printed bracket is needed, a cylindrical 3D printed bracket can be prepared directly by 3D printing, or the aforementioned cube 3D printed bracket can be cut into a cylinder by a hole puncher.
[0057] (3) Immersing the cube-shaped and cylindrical 3D printed stents in a dopamine Tris-HCl buffer solution with a pH of 8.5 and a dopamine concentration of 20 mol / L, and taking them out after 24 hours, thereby obtaining a 3D printed stent with a polydopamine coating; the dopamine Tris-HCl buffer solution is obtained by dissolving dopamine in a Tris-HCl buffer solution, the concentration of the Tris-HCl buffer solution is 10 mmol / L, and the pH is 8.5.
[0058] Example 3
[0059] In this embodiment, a montmorillonite-reinforced hybrid fiber-bonded 3D printed implant is prepared in the following steps:
[0060] (1) The HAD prepared in Example 1 was dissolved in ultrapure water to obtain a HAD solution with a concentration of 25 mg / mL. Type I collagen from cowhide was dissolved in 0.5 mol / L acetic acid solution to obtain a type I collagen solution with a concentration of 25 mg / mL.
[0061] (2) The HAD solution and type I collagen solution were thoroughly mixed in an ice bath at a volume ratio of 1:1 under stirring, and then montmorillonite (MMT) with a size not exceeding 50 μm (SEM image of which is shown in FIG. Figure 1As shown in the figure, the mass ratio of HAD, type I collagen and micron-sized montmorillonite is 1:1:0.02, which are fully stirred and dispersed evenly, and then 1 mol / L NaOH solution is added to the obtained mixed solution under stirring conditions to adjust the pH value to 7.2 to form a sol.
[0062] (3) Immediately take the 3D printed stent with polydopamine coating prepared in step (3) of Example 2 and quickly immerse it in the sol, so that the sol fills the pores of the 3D printed stent with polydopamine coating. During this process, pay attention to whether bubbles appear in the sol. If bubbles appear, use a syringe to remove the bubbles. Then, the 3D printed stent with polydopamine coating filled with sol in the pores is placed at 4°C for 12 hours, and the sol is converted into a gel state, and then freeze-dried to obtain a montmorillonite-reinforced hybrid fiber bonded 3D printed implant, recorded as PGK.
[0063] Comparative Example 1
[0064] In this comparative example, the 3D printed stent with a polydopamine coating prepared in step (3) of Example 2 was immersed in a PBS buffer solution, taken out after 12 hours, and freeze-dried to obtain a control implant 1, which was recorded as PGS.
[0065] Comparative Example 2
[0066] The operation in this comparative example is basically the same as that in Example 3, except that no montmorillonite is added when preparing the sol in step (2), and a control implant 2 is obtained, which is denoted as PGH.
[0067] Thermogravimetric and differential thermal analysis of PGS, PGH and PGK showed the following results: Figures 3-4 As shown in the figure, PGK has a higher solid content than PGS and PGH, and PGK has better thermal stability and a higher solid content than PGH. This is due to the chelation effect between montmorillonite and the organic components in PGK and the intermolecular force.
[0068] XRD test was performed on montmorillonite (MMT) raw materials and PGK, and the results are as follows Figure 5 As shown, Figure 5 The curve in the middle top is the diffraction curve of pure MMT raw material, and the curve in the bottom is the diffraction curve of PGK. Both sets of curves show the diffraction peak of montmorillonite layered structure at 2θ=5.8°. For pure MMT, the characteristic peak of 2θ=5.8° in the XRD diffraction curve of PGK becomes less obvious, and the diffraction peak of PGK shifts. The interlayer spacing is measured according to the Bragg equation, and it is found that the interlayer spacing of montmorillonite is from pure MMT to Became PGK This may be mainly due to the dispersion of montmorillonite in the polymer matrix and the intercalation of polymer in montmorillonite sheets.
[0069] The storage modulus of the hydrogels formed after PGK and PGH were fully swollen in water was tested by dynamic mechanical analyzer (DMA) at different compression frequencies. The dynamic mechanical analysis test results of the two hydrogels are shown in Figure 6 As shown. Figure 6 It can be seen that PGK has significantly higher mechanical strength than PGH, and the storage modulus of PGK is more than 5 times that of PGH. This is mainly caused by the introduction of montmorillonite to increase the bonding degree of the hydrogel.
[0070] Example 4
[0071] In this example, the biological activities of the implants PGK, PGS and PGH prepared in Example 3 and Comparative Examples 1-2 were tested by in vitro cell experiments.
[0072] PGS, PGH and PGK were immersed in the culture medium in the well plate respectively, and the BMSC cell suspension was dripped on each implant drop by drop. After the dripping was completed, the well plate was placed in an incubator and cultured at 37°C and 5% CO2. The culture medium was replaced every 2 days during the culture period. The culture medium was obtained by adding a mixture of penicillin and streptomycin with a mass concentration of 1%, ascorbic acid with a mass concentration of 0.2%, and fetal bovine serum with a mass concentration of 10% to the α-MEM basic culture medium. The penicillin and streptomycin mixture in this embodiment was provided by HyClone.
[0073] The implants were removed after 1, 3, 7, and 14 days of culture, and the proliferation of cells therein was tested using CCK-8. Figure 7 shown.
[0074] After culturing for 1, 3, 7, and 14 days, the implants were removed and washed twice with PBS buffer. The washed implants were immersed in PBS buffer containing FDA and PI for staining for 1 min. The growth state and distribution of cells in 3D were observed by confocal laser scanning microscopy (CLSM). The FDA / PI staining results are shown in Figure 2. Figure 8 shown.
[0075] After culturing for 1, 3, 7, and 14 days, the implants were removed and washed twice with PBS buffer. The washed implants were immersed in a solution containing phalloidin for staining for 4 h, and then stained with a stain containing DAPI for 30 s. The growth state and distribution of cells therein were observed by CLSM. The results of phalloidin / DAPI staining are shown in FIG. Fig. 9 shown.
[0076] Depend on Figure 7It can be seen that as the culture time increases to 7 days, the proliferation of cells in PGK is significantly better than that in PGS and PGH. Figures 8-9 It can be seen that BMSC cells stretch more fully on PGK, have more obvious pseudopodia, and present a typical long spindle shape. This shows that the montmorillonite-reinforced hybrid fiber-bonded 3D printed implant provided by the present invention is conducive to the adhesion and growth of BMSC cells, can promote the proliferation of BMSC cells therein, and has good cell compatibility.
[0077] Example 5
[0078] In this embodiment, a repair experiment of critical-size defects of femoral condyle was performed on rabbits.
[0079] New Zealand white rabbits weighing 2.3-2.6 kg were selected and anesthetized with sodium pentobarbital. After skin preparation, iodine was used for disinfection. A longitudinal incision was made on the lateral side of the distal femur, and the femoral condyle was exposed by blunt separation. The center of the femoral condyle was located, and a hole was slowly drilled in the center with an electric drill. A cylindrical defect was created with an electric drill with a diameter of 7 mm. The hole was infiltrated and rinsed with physiological saline while drilling, and a femoral condyle defect model with a diameter of about 7 mm and a depth of about 10 mm was constructed.
[0080] In this embodiment, an experimental group, a control group and a blank group were set up. The experimental group was implanted with PGK, the control group was implanted with PGH, and the blank group was not implanted with any material. PGK and PGH whose sizes matched the femoral condyle defect model after irradiation and sterilization were implanted into the bone defect site. Then the muscles, fascia and skin were closed layer by layer, the incision was disinfected, and the rats were put back into the cage for continued feeding after waking up. Micro-CT scanning and HE histochemical staining were performed 12 weeks after implantation. The results are shown in the figure. Fig.10 As shown, the first and second columns are Micro-CT scanning test results, and the third column is HE tissue chemical staining results.
[0081] Depend on Fig.10 It can be seen that the femoral condyle defect repair effect in the experimental group was good, and after 12 weeks of repair, the cortical bone part had healed and reshaped completely, with no difference in the morphology of the surrounding host bone tissue, while the control group and the blank group had only a small amount of bone formation and the length of new bone growth was not ideal. In the experimental group, the new bone grew from the defect to the defect center, and the bone integration effect with the implant was excellent.
[0082] The above experimental results show that the montmorillonite-reinforced hybrid fiber-bonded 3D printed implant provided by the present invention has better host bone integration and bone conduction ability, and excellent bone repair performance.
[0083] Example 6
[0084] In this embodiment, a montmorillonite-reinforced hybrid fiber-bonded 3D printed implant is prepared in the following steps:
[0085] (1) HAD with a dopamine grafting rate of 20% was prepared by adjusting the process parameters according to the method of Example 1, and the HAD was dissolved in ultrapure water to obtain a HAD solution with a concentration of 50 mg / mL. Type I collagen from cowhide was dissolved in 0.5 mol / L acetic acid solution to obtain a type I collagen solution with a concentration of 25 mg / mL.
[0086] (2) The HAD solution and the type I collagen solution were fully mixed in an ice bath at a volume ratio of 1:1 under stirring conditions, and then montmorillonite with a size not exceeding 50 μm was added under stirring conditions. The mass ratio of HAD, type I collagen and micron-sized montmorillonite was 1:0.5:0.01. The mixture was fully stirred and dispersed evenly. Then, 1 mol / L NaOH solution was added to the resulting mixture under stirring conditions to adjust the pH value to 7.4 to form a sol.
[0087] (3) Immediately take the 3D printed stent with polydopamine coating prepared in step (3) of Example 2 and quickly immerse it in the sol, so that the sol fills the pores of the 3D printed stent with polydopamine coating. During this process, pay attention to whether bubbles appear in the sol. If bubbles appear, use a syringe to remove the bubbles. Then, the 3D printed stent with polydopamine coating filled with sol in the pores is placed at 4°C for 12 hours, and the sol is converted into a gel state, and then freeze-dried to obtain a montmorillonite-reinforced hybrid fiber-bonded 3D printed implant.
[0088] Example 7
[0089] In this embodiment, a montmorillonite-reinforced hybrid fiber-bonded 3D printed implant is prepared in the following steps:
[0090] (1) HAD with a dopamine grafting rate of 15% was prepared by adjusting the process parameters according to the method of Example 1, and the HAD was dissolved in ultrapure water to obtain a HAD solution with a concentration of 5 mg / mL. Type I collagen from cowhide was dissolved in a 0.5 mol / L acetic acid solution to obtain a type I collagen solution with a concentration of 10 mg / mL.
[0091] (2) The HAD solution and the type I collagen solution were fully mixed in an ice bath at a volume ratio of 1:1 under stirring conditions, and then montmorillonite with a size not exceeding 50 μm was added under stirring conditions. The mass ratio of HAD, type I collagen and micron-sized montmorillonite was 0.5:1:0.03. The mixture was fully stirred and dispersed evenly. Then, 1 mol / L NaOH solution was added to the resulting mixture under stirring conditions to adjust the pH value to 7.0 to form a sol.
[0092] (3) Immediately take the 3D printed stent with polydopamine coating prepared in step (3) of Example 2 and quickly immerse it in the sol, so that the sol fills the pores of the 3D printed stent with polydopamine coating. During this process, pay attention to whether bubbles appear in the sol. If bubbles appear, use a syringe to remove the bubbles. Then, the 3D printed stent with polydopamine coating filled with sol in the pores is placed at 4°C for 12 hours, and the sol is converted into a gel state, and then freeze-dried to obtain a montmorillonite-reinforced hybrid fiber-bonded 3D printed implant.
Claims
1. A montmorillonite reinforced hybrid fiber bonded 3D printed implant, characterized in that: The implant is composed of a 3D printed stent with a polydopamine coating and a hybrid fiber reinforced by montmorillonite. The 3D printed stent with a polydopamine coating has micron-sized macropores that are interconnected. The hybrid fiber reinforced by montmorillonite is combined with the 3D printed stent with a polydopamine coating and distributed in the micron-sized macropores of the 3D printed stent with a polydopamine coating, forming micron-sized small pores in the micron-sized macropores. The 3D printed stent with polydopamine coating is composed of a 3D printed stent and a polydopamine coating on the surface of the 3D printed stent, and the 3D printed stent is composed of components including a 3D printed polymer material and micron-sized hydroxyapatite; The montmorillonite-reinforced hybrid fiber is a polymer network formed by oxidation self-crosslinking of a polymer material having a catechol functional group, Michael addition reaction of the polymer material having a catechol functional group and collagen, chelation of phenolic hydroxyl groups of micron-sized montmorillonite and the polymer material having a catechol functional group, and hydrogen bonding or / and electrostatic interaction between the micron-sized montmorillonite, collagen and the polymer material having a catechol functional group; a part of the Michael addition reaction product of the polymer material having a catechol functional group and collagen and the oxidation self-crosslinking polymer material having a catechol functional group are intercalated into the montmorillonite sheets; The polydopamine coating on the surface of the 3D printed stent with the polydopamine coating is bonded to the collagen in the montmorillonite-reinforced hybrid fiber and the polymer material with catechol functional groups through Michael addition reaction and oxidative cross-linking reaction, respectively. The polydopamine coating on the surface of the 3D printed stent with the polydopamine coating is bonded to the micron-sized montmorillonite in the montmorillonite-reinforced hybrid fiber through chelation, hydrogen bonding or / and electrostatic action. The montmorillonite-reinforced hybrid fiber is formed by reacting a polymer material having a catechol functional group, collagen and micron-sized montmorillonite in a mass ratio of (0.5-1):(0.5-1):(0.01-0.03); the 3D printed scaffold with a polydopamine coating is formed by soaking the 3D printed scaffold in a dopamine Tris-HCl buffer solution with a pH value of 8.5-8.8 and a dopamine concentration of 20-50 mol / L for 15-30 h; in the 3D printed scaffold, the content of micron-sized hydroxyapatite is 50 wt.%-90 wt.%; the micron-sized hydroxyapatite is a spherical particle with a particle size not exceeding 50 μm, and the size of the micron-sized montmorillonite is not more than 50 μm. μm; the polymer material with catechol functional groups is formed by grafting dopamine on a biocompatible polymer material, the grafting rate of dopamine on the biocompatible material is 5%~40%, the molecular weight of the biocompatible polymer material as the basis for dopamine grafting modification is 100~2000 kDa, the polymer material with catechol functional groups includes at least one of dopamine-modified hyaluronic acid, dopamine-modified silk protein and dopamine-modified gelatin; the 3D printing polymer includes at least one of polylactic acid-co-glycolic acid, polycaprolactone, polyvinyl alcohol and polydimethylsiloxane; the collagen is type I collagen; the size of the micron-sized macropores is 500~1200 μm, and the size of the micron-sized small pores is 100~200 μm.
2. The montmorillonite-reinforced hybrid fiber-bonded 3D printed implant according to claim 1, characterized in that: The content of the montmorillonite-reinforced hybrid fiber in the implant is 20 wt.% to 30 wt.%.
3. The method for preparing the montmorillonite-reinforced hybrid fiber-bonded 3D printed implant according to claim 1 or 2, characterized in that: The following steps are involved: (1) The dried 3D printed scaffold is fully immersed in a dopamine Tris-HCl buffer solution with a pH value of 8.5 to 8.8 to obtain a 3D printed scaffold with a polydopamine coating; (2) dissolving the polymer material having catechol functional groups and collagen respectively, fully mixing the obtained solution of the polymer material having catechol functional groups, the obtained collagen solution and micron-sized montmorillonite, and then adjusting the pH value to 7.0-7.4 to form a sol; (3) Immersing the polydopamine-coated 3D printed stent in the sol to allow the sol to fill the pores of the polydopamine-coated 3D printed stent, allowing the polydopamine-coated 3D printed stent with the pores filled with the sol to stand until the sol is transformed into a gel state, and freeze-drying to obtain a montmorillonite-reinforced hybrid fiber-bonded 3D printed implant.
4. The method for preparing the montmorillonite-reinforced hybrid fiber-bonded 3D printed implant according to claim 3, characterized in that: The preparation method of the 3D printed bracket is as follows: fully dispersing components including 3D printed polymer and micron-sized hydroxyapatite in a solvent, and volatilizing and removing part of the solvent to obtain a 3D printed slurry, making the 3D printed slurry into a bracket by 3D printing, and removing moisture from the bracket to obtain a 3D printed bracket.
5. Use of the montmorillonite-reinforced hybrid fiber-bonded 3D printed implant according to claim 1 or 2 in the preparation of bone repair materials.
Citation Information
Patent Citations
Functionalized fiber macromolecule cross-linking body bonded 3D printing elastic implant and preparation method and application thereof
CN114588312A